The Impact of Mycobacterium avium subsp. paratuberculosis on Intestinal Microbial Community Composition and Diversity in Small-Tail Han Sheep - Shi-Yuan Xue; Wei Ma; Meng-Yuan Li; Wei-Kang Meng; Yu-Lin Ding; Bo Yang; Yue-Rong Lv; Rui-Bin Chen; Zhi-Hong Wu; Siqin Tunala; Rong Zhang; Li Zhao; et al. (Pathogens)
Paratuberculosis (PTB), primarily caused by Mycobacterium avium subsp. paratuberculosis (MAP), is a chronic infection that affects ruminants and is difficult to prevent, diagnose, and treat. Investigating how MAP infections affect the gut microbiota in sheep can aid in the prevention and treatment of ovine PTB. This study examined fecal samples from eight small-tail Han sheep (STHS) at various stages of infection and from three different field areas. All samples underwent DNA extraction and 16S rRNA sequencing. Among all samples, the phyla p. Firmicutes and p. Bacteroidota exhibited the highest relative abundance. The dominant genera in groups M1–M6 were UCG-005, Christensenellaceae_R-7_group, Rikenellaceae_RC9_gut_group, Akkermansia, UCG-005, and Bacteroides, whereas those in groups A–C were Christensenellaceae_R-7_group, Escherichia–Shigella, and Acinetobacter, respectively. The microbial community structure varied significantly among groups M1–M6. Specifically, 56 microbiota consortia with different taxonomic levels, including the order Clostridiales, were significantly enriched in groups M1–M6, whereas 96 microbiota consortia at different taxonomic levels, including the family Oscillospiraceae, were significantly enriched in groups A–C. To the best of our knowledge, this is the first study to report that MAP infection alters the intestinal microbiota of STHS. Changes in p. Firmicutes abundance can serve as a potential biomarker to distinguish MAP infection and determine the infection stage for its early diagnosis. Our study provides a theoretical basis for the treatment of PTB by regulating the intestinal microbiota, including p. Firmicutes.